Efficient Output Solution for Nonlinear Stochastic Optimal Control Problem with Model-Reality Differences - Kek, S.L.; Teo, Kok Lay; Aziz, M. (Gordon and Breach, 2015)
A computational approach is proposed for solving the discrete time nonlinear stochastic optimal control problem. Our aim is to obtain the optimal output solution of the original optimal control problem through solving the simplified model-based optimal control problem iteratively. In our approach, the adjusted parameters are introduced into the model used such that the differences between the real system and the model used can be computed. Particularly, system optimization and parameter estimation areintegrated interactively. On the other hand, the output is measured fromthe real plant and is fed back into the parameter estimation problemto establish amatching scheme.During the calculation procedure, the iterative solution is updated in order to approximate the true optimal solution of the original optimal control problem despite model-reality differences. For illustration, a wastewater treatment problem is studied and the results show the efficiency of the approach proposed.